Easy and versatile coating approach for long-living white hybrid light-emitting diodes - Niklaus, Lukas; Dakhil, Haider; Kostrzewa, Monika Maria; Brana Coto, Pedro; Sonnewald, Uwe; Wierschem, Andreas; Costa Riquelme, Rubén Dario (Materials Horizons, 2016)
Herein, we provide a new easy-to-do protocol for preparing luminescent rubber-like materials based on a wide palette of compounds, such as small-molecules, quantum dots, polymers, and coordination complexes. The combination of this new protocol with that for preparing similar rubbers based on fluorescent proteins states the universal character of our approach. This is further assessed by using comprehensive spectroscopic and rheological investigations. Furthermore, the novel luminescent rubbers are applied as downconverting packing systems to develop white hybrid light-emitting diodes (WHLEDs), which are heralded as a solid alternative to achieve energy-saving, solid-state, and white-emitting sources in the coming future. As such, the current work also provides a clear prospect of this emerging lighting technology by means of a direct comparison among WHLEDs fabricated with all the above-mentioned down-converting systems. Here, the use of rubbers based on coordination complexes outperforms the others in terms of both luminous efficiency and colour quality with an unprecedented stability superior to 1000 h under continuous operation conditions. This represents an order of magnitude enhancement compared to the state-of-the-art WHLEDs, while keeping luminous efficiencies of around 100 lm W-1.

Interactions between falling spheres in the wormlike micellar solutions - Kostrzewa, Monika Maria; Broniarz-Press, Lubomira; Delgado, Antonio; Wierschem, Andreas (Advances in Modern Mechanical Engineering, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.ITC.stmmec.intera

Micropatterned Down-Converting Coating for White Bio-Hybrid Light-Emitting Diodes - Niklaus, Lukas; Tansaz, Samira; Dakhil, Haider; Weber, Katharina; Pröschel, Marlene; Lang, Martina; Kostrzewa, Monika Maria; Coto, Pedro B.; Detsch, Rainer; Sonnewald, Uwe; Wierschem, Andreas; Boccaccini, Aldo R.; et al. (Advanced Functional Materials, 2017)
White hybrid light-emitting diodes (WHLEDs) are considered as a solid approach toward environmentally sustainable lighting sources that meet the "Green Photonics" requirements. Here, WHLEDs with protein-based down-converting coatings, i.e., Bio-WHLEDs, are demonstrated and exhibit worthy white color quality, luminous efficiency, and stability values. The coatings feature a multilayered cascade-like architecture with thicknesses of 1-3 mm. This limits the efficiency due to the low optical transmittance. Thus, submillimeter coatings, where the location of the proteins is well-defined, are highly desired. It is in this context where the thrust of this work sets in. Here, a straightforward way to design microstructured single-layer coatings, in which the proteins are placed at our command by using 3D printing, is presented. Based on comprehensive spectroscopic and rheological investigations, the optimization of the matrix and the plotting to prepare different micropatterns, i.e., lines, open-grids, and closed-grids, is rationalized. The latter are applied to prepare Bio-WHLEDs with approximate to 5-fold enhancement of the luminous efficiency compared to the reference devices with a cascade-like coating, without losing stability and color quality. As such, this work shows a new route to exploit proteins for optoelectronics, setting a new avenue of research into the emerging field of Bio-WHLEDs.

Particle settling in micellar solutions of varying concentration and salt content - Kostrzewa, Monika Maria; Delgado, Antonio; Wierschem, Andreas (Acta Mechanica, 2016)
The effect of concentration and molar ratio of cetyltrimethylammonium bromide with sodium salicylate (CTAB/NaSal) micellar aqueous solutions on the settling of non-Brownian spheres is determined. The micelles cause shear thinning, which may result in a shear-stress plateau. The measurements were performed in the wide range of Weissenberg numbers showing drag reduction and enhancement. Maximum drag coincides with the minimum relaxation time. For equimolar solutions, a correlation between Weissenberg number and normalized drag correction factor is proposed. The average settling velocity decreases proportionally to the inverse CTAB/NaSal concentration squared and is closely related to the micellar network size. Salt excess in 10 mM CTAB solutions results in an exponential increase in the average velocity. We find steady and unsteady regimes for the particle motion. In equimolar solutions, the frequency decreases with the concentration, whereas the dominant frequency does not change with salt excess, but is associated with the shear-stress oscillations. We show that the unsteady particle motion is related to the rheological time-dependent properties of the micellar solutions.
UnivIS-Import:2016-02-10:Pub.2015.tech.ITC.stmmec.partic
Keywords: Brownian movement; Drag; Shear stress; Shear thinning; Cetyl trimethyl ammonium bromides; Correction factors; Dominant frequency; Exponential increase; Non-Brownian spheres; Time-dependent properties; Weissenberg number

Polyoxometalate ionic liquids as self-repairing acid-resistant corrosion protection - herrmann, sven; Kostrzewa, Monika Maria; Wierschem, Andreas; Streb, Carsten (Angewandte Chemie International Edition, 2014)
Corrosion is a global problem for any metallic structure or material. Herein we show how metals can easily be protected against acid corrosion using hydrophobic polyoxometalate-based ionic liquids (POM-ILs). Copper metal disks were coated with room-temperature POM-ILs composed of transition-metal functionalized Keggin anions [SiW11O39TM-(H2O)]n- (TM=CuII, FeIII) and quaternary alkylammonium cations (CnH2n+1)4N+ (n=7-8). The corrosion resistance against acetic acid vapors and simulated "acid rain" was significantly improved compared with commercial ionic liquids or solid polyoxometalate coatings. Mechanical damage to the POM-IL coating is self-repaired in less than one minute with full retention of the acid protection properties. The coating can easily be removed and recovered by rinsing with organic solvents.
UnivIS-Import:2015-03-09:Pub.2014.tech.ITC.stmmec.polyox
Keywords: Corrosion; Ionic liquid; Metal oxides; Polyoxometalate; Self-assembly

Polyoxometallat-basierte ionische Flüssigkeiten als selbstreparierender Säure-Korrosionsschutz - Herrmann, Sven; Kostrzewa, Monika Maria; Wierschem, Andreas; Streb, Carsten (Angewandte Chemie, 2014)
UnivIS-Import:2015-04-02:Pub.2014.tech.ITC.stmmec.polyox_7